Les analphabètes au Maroc : un groupe homogène en demande d'alphabétisation ? - Sophie Cerbelle (Les éditions de la Maison des sciences de l'Homme, 2013)
This article examines the results of a research carried out in Morocco, in Marrakech academy in 2007 among beneficiaries of literacy programs. Qualitative and quantitative methods are being mobilized to show the diversity of the motivations leading people to register in training programs that are strongly correlated to personal characteristics such as age, geographical origins or gender. The analysis shows that registration does not only result from their wish to gain basic literacy and numeracy skills and their hope to join the labour market but also from other types of motivations such as the search for novelty, the willingness to meet new people or a way to escape from boredom. This diversity questions traditional discourses on literacy focusing on literacy skills as a basic need which contributes to the stigmatization of illiterate people.